Impact of coronavirus pandemic crisis in endoscopic clinical practice: Results from a national survey in Brazil - Arantes, Vitor Nunes; Martins, Bruno Costa; Seqatto, Raphael; Milhomen-Cardoso, Daniela Medeiros; Franzini, Tomazo Prince; Zuccaro, Anna Maria; Alves, Jairo Silva; Maluf-Filho, Fauze (Endoscopy International Open, 2020)
Background and study aims In March 2020, the World Health Organization declared coronavirus disease of 2019 (COVID-19) as a pandemic, mobilizing all countries to contain the disease spread. Activity in endoscopy centers globally was severely affected. We conducted a national survey aiming to assess the impact of the COVID-19 outbreak on endoscopic clinical practice in Brazil.Methods In April 2020, 3,719 associate members of SOBED (Brazilian Society of Digestive Endoscopy) were invited to respond to an electronic survey. An Internet link was established to provide access to the online questionnaire with 40 questions regarding personal profile, endoscopy unit logistics and schedule, availability and use of personal protective equipment (PPE), financial impact, and exposure to COVID-19.Results A total of 2,131 individuals (67 %) accessed the questionnaire and 1155 responses were received. After review, 980 responses were considered valid. According to almost 90 % of respondents, endoscopy activity was restricted to urgent procedures, in both public and private hospitals. All respondents increased PPE use after the outbreak, however, institutions provided adequate PPE to only 278 responders (28.7 %). Significant income loss was universally reported. A total of 10 practitioners (1 %) reported COVID-19 infection and attributed the contamination to endoscopic procedures.Conclusions Based on this nationwide survey with almost 1,000 respondents, the COVID-19 pandemic substantially reduced the activity of endoscopy units in private and public settings. The pandemic increased awareness of PPE use, but its availability was not universal and 1 % of the respondents became infected with COVID-19, allegedly due to exposure during endoscopic procedures.